Research Priorities for Improvement of Rangelands - Paroda, R S; Mal, Bhag (Annals of Arid Zone, 2016)
Pasture lands are major landuse systems in arid and semi-arid regions. These rangelands are being over-exploited due to increased livestock pressure leading to rapid depletion of natural vegetation. Immediate measures are, therefore, required for developing adequate location-specific management strategies for their rehabilitation and improvement in order to have sustained production. Some areas of research that need priority attention are focused.